Eco-enzyme Disinfection in Pig Housing as an Effort to Suppress Esherechia coli Population - N. Ginting; Hasnudi Hasnudi; Yunilas Yunilas (Jurnal Sain Peternakan Indonesia, 2021)
Pig farms are susceptible to infection by Escherechia coli bacteria which causes Colibacillosis. A dirty cage is one of the causes. This can be prevented by disinfection. Eco- enzymes are fermented fruits that contain enzymes and are anti-microbial. This study aims to find a dilution of Eco- enzyme that can suppress the population of Escherechia coli in pig pens. The study was carried out in two stages, first was in in vitro to find the best treatment and second was in in vivo to determine the decrease in the population of E. coli in pig pens after disinfection with Eco-enzymes. The in vitro treatments were P1: Eco enzyme diluted 1:10; P2 1:20 and P3 1:30. Parameters are the area of the inhibition zone and the antimicrobial index. In an in-vivo study, the data taken were the population of E. coli on the floor of the cage and in the waterways before and after disinfection. The results showed that Eco enzyme diluted 1:30 had the best inhibition zone and antimicrobial index. Disinfection of pig pens using Eco-enzyme dilution of 1:30 was successful in reducing the population of E.coli in pig pens.